The Vedic “Ocean of Heart”: Some Associations of the Image - Razauskas, Dainius (Acta Orientalia Vilnensia, 2003)
The image of the “ocean of heart” occurs in Rigveda IY.58.5 (sacrifice flows hṛ́dyāt samudrā́t “from the ocean of heart”), 11 (sacrifice grounds everything samudré hṛdy àntár ā́yuṣi “in the ocean, in the heart, in the midst of life”); X.5.1 (ékaḥ samudró dharúṇo rayīṇā́m asmád dhṛdó bhū́rijanmā ví caṣṭe “the one ocean, the bearer of riches, the producer of many, speaks from our heart”) and, according to J. Gonda and T. J. Elizarenkova, may be traced in X.177.1, perhaps also in 1.159.4. Firstly, as is well known and has been exhaustively shown by J. Gonda, the Vedic concept of the heart comprises the wide range of psychological meanings, such as (spiritual) perception, cognition, comprehension, sensation, intuition, vision etc., and, as H. Grassmann has already observed, is often paralleled by mānas-. (Such psychologically broadened concept of the heart is widespread and usual almost all over the world.) This allows us to look at the Vedic “ocean of heart” as an “ocean of soul”. Secondly, the meaning ‘ocean’ ascribed to Vedic samudrá- is quite arbitrary. The word consists of prefix sam- and the heteroclytic noun udán- ‘water’ (cf. its cognates Lettish udens, Lith. vanduō, -eñs ‘water’ etc.). Therefore, the Vedic samudrá- may be defined more broadly as ‘(large) body of water’ including ‘ocean’, ‘sea’, ‘lake’ etc. This, then, immediately reminds us of Germanic words for ‘soul’ (English soul, German Seele etc.) deriving from *saiwalō, which, in its turn, comes from *saiwaz ‘see, lake’, represented in English sea, German die See ’sea’, der See ‘lake’ etc. From the other part of the world, cf. description of the trigram “Lake” from the Chinese I ling (“The Book of Changes”) by Lama Anagarika Govinda: “[...] the Lake gives joy to the heart of man by responding to the smallest as well as to the largest thing, mirroring his world and his emotions through the transparent medium of its shining surface”. Expressive examples of the image of “reflecting surface of the soul” may be found, among others, in Taoist sources up to our days. In modern analytical psychology the images of the lake and of the sea are well known symbols of the soul too, namely of the collective unconscious, and partly quite for the same reason. In the words of C. G. Jung, “the sea is the symbol of the collective unconscious, because unfathomed depths lie concealed beneath its reflecting surface”. According to Marie-Louise von Franz, “the symbolisation of the unconscious by water with its mirror like surface is of course based in the final analysis on a projection. Nevertheless, the analogies are astonishingly meaningful. Just as we cannot ‘sce’ into the depths of the waters, so the deeper areas of the unconscious are also invisible to us; we can draw only indirect conclusions about them. But on the surface, on the threshold area between consciousness and the unconscious, dream images appear spontaneously, not only seeming to give us information about the depths but also mirroring our conscious personality”. Cf. also Mary M. Watkins: “Water itself originates no movement but is itself infinitely movable. It is able to receive and record impressions. Its colorlessness, odorlessness, and shapelessness make it the perfect element against which one can see other things. In order for us to be more receptive to the imaginal we can pretend that apart of us must become more like water. That would first mean that it must learn to cease the movement it itself originates. We are all the time initiating movement by thinking thoughts, doing activities, being involved in daydreams. We rise and fall, flow, and swirl. [...] When part of us tries to become as water it gains (through its own cessation of initiating movement) the ability to reflect. [...] You can actually pretend you are a body of water. At first notice how your usual thoughts and preoccupations create waves and ripples - flowing, curling, whirling activity. Gradually try to become still. Your ripples become slower and steadier. Feel yourself in these ripples”. As the ripples and waves on the surface of water destroy its capacity to reflect so the ripples and waves of soul hinder the mind’s capacity of reflection. Cf. in this sense the main Russian verb for ‘agitation, excitement’ волноваться, originally meaning namely ‘to rise in waves, to wave’ (from the noun волнá ‘wave’). Essentially the same image we find in Hinduist speculations on the concept of vṛttis as waves of consciousness producing kleśas and hindering the direct perception of the Self, as also in the similar images concerning the Buddhist ālaya vijn̄āna equated by Th. Stcherbatsky to the Western psyche, etc. After all, the Vedic udán- ‘water’ consisting in samudrá- can itself acquire the meaning ‘wave’ as, for instance, has appropriated its cognate Latin unda. We can maintain, therefore, that the Vedic “ocean of heart” has for its ground the same ancient and widespread (archetypal?) image of reflecting soul as a body of water reaching, as we can guess from its Germanic an Slavic examples, the Indoeuropean antiquity. Moreover, the same image expressed almost in the same words as the Vedic one occurs in Dante’s nel lago del cor “in the lake of (my) heart” (Inferno I.20). That at least makes an impression, independently of its particular relation to the Vedic equivalent.